2021
DOI: 10.1029/2020gc009202
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior and Inferred Seismic Properties of Tonalitic Migmatites at the Time of Pre‐melting, Partial Melting, and Post‐Solidification

Abstract: As seismic data from the lower crust becomes more readily available, it is important to link seismic properties to the ongoing processes within lower crustal evolution. This includes high temperature, pre‐ and post‐migmatization solid state deformation as well as melt‐present deformation. We selected two tonalitic migmatites with variable former melt content (one metatexite and one diatexite) from the lower crustal Daqingshan area, northern North China Craton to assess the link between seismic properties and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 119 publications
0
7
3
Order By: Relevance
“…This observation is not in agreement with that of Shao et al. (2021), wherein the reported neosomes (melt‐derived phases) are weakly strained than the residuum (pre‐melt phases). Shao et al.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This observation is not in agreement with that of Shao et al. (2021), wherein the reported neosomes (melt‐derived phases) are weakly strained than the residuum (pre‐melt phases). Shao et al.…”
Section: Discussioncontrasting
confidence: 97%
“…The GOS further reveals that all the melt-derived phases are more strained (higher RMS GOS value) than quartz (RMS GOS = 0.35°), which is one of the starting materials. This observation is not in agreement with that of Shao et al (2021), wherein the reported neosomes (melt-derived phases) are weakly strained than the residuum (pre-melt phases). Shao et al (2021) report that the deformation was partitioned into the melt and consequently the solid phases had weaker CPOs than the minerals strained during pre-melt conditions.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The GOS further reveals that all the melt-derived phases are more strained (higher RMSGOS value) than quartz (RMSGOS = 0.35°), which is one of the starting materials. This observation is not in agreement with that of Shao et al (2021), wherein the reported neosomes (melt-derived phases) 15 are weakly strained than the residuum (pre-melt phases). Shao et al (2021) report that the deformation was partitioned into the melt and consequently the solid phases had weaker CPOs than the minerals strained during pre-melt conditions.…”
Section: Discussioncontrasting
confidence: 77%
“…The existing deformation models of partially molten rocks, mostly derived from studying migmatites, illustrate that (a) both melt and melt-crystallized phases are strained during the synmelting and late-stage solid state deformation, respectively (Prakash et al, 2018) 5 creep accommodates strain during both pre-and post-melt conditions, but dissolutionprecipitation and rigid body rotation dominate under melt-present deformation (Shao et al, 2021); (c) in-situ coarsening is followed by dislocation creep of grains nucleating from the melt (Lee et al, 2020); (d) fine grain size and water saturated conditions favor diffusion creep (Dell'Angelo & Olgaard, 1995;Kilian et al, 2011), whereas presence of melt favors grain boundary sliding (Lee et al, 2018;Stuart et al, 2018); and (e) the minerals crystallized from the melt may deform by dislocation creep (Miranda & Klepeis, 2016). Crystallographic preferred orientations (CPOs) are generally developed during dislocation creep and therefore provide constrains on the predominant deformation mechanisms.…”
Section: Introductionmentioning
confidence: 99%